Edukasi Pengelolaan Obat Melalui Dagusibu di Padukuhan Ngentak, Sumberagung, Jetis, Bantul, Yogyakarta - Sugiyono Sugiyono; Niken Larasati (Kreativasi : Journal of Community Empowerment, 2023)
People are increasingly using various drugs for health purposes, influenced by factors like disease prevalence, expanded medication options, and improved access through national health insurance. These developments have both positive and negative effects. On the positive side, more people are taking better care of their health by seeking medical attention. However, the negative consequence of increased drug use includes potential errors in usage and disposal due to insufficient public education. These errors can harm individuals and the environment. Community service in Padukuhan Ngentak, Sumberagung, Jetis, Bantul, Yogyakarta, focuses on educating residents about Dagusibu (Get-Use-Save-Dispose). It employs education, counseling, discussions, and material reviews. The goal is to enhance public knowledge of Dagusibu to ensure proper medication acquisition, usage, and storage, preventing environmental harm from improper drug waste disposal. The process involves three phases: pretest, lecture-based information delivery, and postest evaluation. Community service activities can run smoothly and the community follows enthusiastically. The number of residents who participated in this activity was 33 people. Based on the assessment of the level of pretest and postest knowledge using questionnaires, it showed an increase in the good category by 78.79%. These results show an increase in citizen knowledge and this is expected to have an impact on public health.